TECNOLOGIA EDUCACIONAL PARA PROMOÇÃO DE PRÁTICAS PARENTAIS POSITIVAS EM SAÚDE MATERNO-INFANTIL - Cerezer, Julia Piccin (2024)
Introduction: In municipal schools, discussions about positive parenting are still scarce, which reinforces the need for initiatives that promote accessible and relevant information on the subject for parents and educators. This study emerges as a contribution to fill this gap through the creation of a playful material called “ParentAções”, an interactive educational technology designed to assist psychologists and parenting educators in providing practical guidance to parents and educators in different contexts that seeks to promote healthier family and educational environments. Objectives: to develop an interactive educational technology in the form of a case card designed to assist psychologists and parenting educators in providing practical guidance to parents and to carry out the ecological validation of the product. The resource developed uses fictitious cases as an active teaching methodology, providing practical support to caregivers and stimulating reflections on their educational practices, which seeks to support caregivers, enabling them to adopt positive educational practices. Caregivers face urgent challenges in the task of educating their children and, therefore, it is essential to offer adequate guidance and support. Methodological Approach: The creation of case cards is based on the Case Study Method and has the potential to be an innovative tool for psychologists working in schools, facilitating their work. The cards were designed to allow the exploration of fictitious situations, stimulating reflection and group debates. The instrument consists of 17 cards and an explanatory manual. The development and implementation of the resource are directly aligned with the Sustainable Development Goals (SDGs) of the UN 2030 Agenda. SDG 4 (Quality Education), SDG 5 (Gender Equality) and SDG 16 (Peace, Justice and Strong Institutions) are met by strengthening violence prevention and fostering safer and more inclusive communities. Ecological insertion was chosen for access in a real context. Results: the data collected were analyzed qualitatively, identifying strengths, challenges and opportunities for improving the resource. The ecological validation consisted of verifying the effectiveness of the material in promoting positive educational practices, based on a qualitative assessment of the experiences reported by the participants. The participants had access to information about positive educational practices and that this information and exchange of experiences with caregivers enabled reflections on their behaviors. Technological product and its applicability: This is an educational technology that was lacking in the work of psychologists and educators in the clinical and school settings. It has a high potential impact and is replicable, and can be adapted to more contexts and realities. It is in the process of registration with the INPI. Final considerations: It is expected that the resource will be replicated and that city governments will implement parental and pedagogical education groups in early childhood education schools as part of the school calendar. In addition, the expectation is that the validation study will contribute to the formulation of effective implementation strategies, promoting the confidence of interested parties in its replicability.